Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-19 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
The outcome of a SCI repair depends strongly on the severance of the injury. A-D. MRI's of approximately 99, 95 and 50% injury. C shows the 50% injury with titan fixation and B without. The severance of an injury can also be estimated with a fixation in place. G,H. In 50% injury, the patient can relearn walking, running and jumping. E,F. In 95% (and 99%) the patient cannot re-learn free walking and jumping.